(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2013)
In today’s era the issue of food security is gaining much more attention as food is one of the three basic requirements of man and is still a serious issue for many poor people. Ensuring food security is a big challenge due to increase in population, climate change etc. especially in developing Asian countries like India. The present study is significant in a way that it examines the variations in spatial patterns of food security at district level in one of the food bowl states of India namely Haryana. This study also tries to identify the factors behind the spatial variations in food security. Despite being self-sufficient in foodgrains production, the state has vast regional contrasts in terms of land productivity, farm labour and standard of living. At present, food grains production is almost stagnant in the state and natural resources are also experiencing degradation due to their extensive use. For this study, secondary data have been collected from various state government offices. Further food availability, food accessibility and food utilization indices have been calculated by using different indicators. The results of the study reveal that the districts situated in central and north-west part of the state having better agricultural infrastructure are more food secure than the districts situated in southern and northern parts of the state which have the disadvantageous the state which have sandy soil, poor irrigation facilities and undulating topography.